Zum palmyrenischen Handelsnetz im Westen - Schleicher, Frank (Anabasis. Studia Classica et Orientalia, 2022)
The study of Palmyrene trade has a long tradition. Numerous inscriptions tell of trading activities, caravan routes and trading posts of the Palmyrenes within and beyond the borders of the Imperium Romanum. While eastern trade has always received a great deal of attention in research and it is communis opinio that the caravans could rely on Palmyrene communities in the cities along the eastern trade routes, Palmyrene activities in the west – from the Mediterranean to Britain – have so far been largely ignored in research. Only a participation in the transport of goods from Palmyra to the coast of the Mediterranean has been conceded to the Palmyrenes. In fact, however, there is circumstantial evidence that suggests the existence of Palmyrene communities in the west as well. Researchers have known about the evidence for a long time, but have never regarded it as proof of an overarching trade network. Closer examination reveals evidence of Palmyrene activities throughout the Western Empire, often linked to trade activities. This article is an attempt to present the old and new evidence from Rome, Dacia, Numidia and Britain, to place it in a common context and – as far as possible – to trace the connections of the western Palmyrenean trade network. Since trade activities are not so easy to grasp archaeologically, a close relationship between Palmyrene sanctuaries outside Palmyra and trade is assumed. The first section of the study describes the connection between sanctuary and trade. In the second section, the known Palmyrene communities in the Mediterranean (and Britannic) area are examined for possible links to trade. Although the study impressively shows that the Palmyrenes were involved in trade activities throughout the Imperium Romanum, we conclude that – based on current knowledge – we cannot identify connections between the nodes of the trade network and can only speculate about trade routes and goods.